Biocompatible mannosylated endosomal-escape nanoparticles enhance selective delivery of short nucleotide sequences to tumor associated macrophages. Issue 2 (19th November 2014) - Ortega, Ryan A.; Barham, Whitney J.; Kumar, Bharat; Tikhomirov, Oleg; McFadden, Ian D.; Yull, Fiona E.; Giorgio, Todd D.
Abstract : Mannosylated nanoparticles are capable of delivering nucleotide sequences to tumor associated macrophages (TAMs) and have enhanced in vivo uptake in TAMs. Abstract : Tumor associated macrophages (TAMs) can modify the tumor microenvironment to create a pro-tumor niche. Manipulation of the TAM phenotype is a novel, potential therapeutic approach to engage anti-cancer immunity. siRNA is a molecular tool for knockdown of specific mRNAs that is tunable in both strength and duration. The use of siRNA to reprogram TAMs to adopt an immunogenic, anti-tumor phenotype is an attractive alternative to ablation of this cell population. One current difficulty with this approach is that TAMs are difficult to specifically target and transfect. We report here successful utilization of novel mannosylated polymer nanoparticles (MnNP) that are capable of escaping the endosomal compartment to deliver siRNA to TAMs in vitro and in vivo . Transfection with MnNP-siRNA complexes did not significantly decrease TAM cell membrane integrity in culture, nor did it create adverse kidney or liver function in mice, even at repeated doses of 5 mg kg −1 . Furthermore, MnNP effectively delivers labeled nucleotides to TAMs in mice with primary mammary tumors. We also confirmed TAM targeting in the solid tumors disseminated throughout the peritoneum of ovarian tumor bearing mice following injection of fluorescently labeled MnNP-nucleotide complexes into the peritoneum. Finally, we show enhanced uptake of MnNP in lung metastasis associated macrophages compared to untargeted particles when using an intubation delivery method. In summary, we have shown that MnNP specifically and effectively deliver siRNA to TAMs in vivo .